Anal HPV preva lence in a cohort of individuals infected with HIV-1 - Nicol, Alcina Frederica; Oliveira, Nathalia Silva; Provance Jr, David William; Friedman, Ruth K.; Veloso, Valdileia Gonçalves; Coutinho, Jose Ricardo; Cunha, Cynthia Braga da; Ferreira, Dennis de Carvalho (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Human Papillomavirus (HPV) is the primary etiologic agent of anogenital tract cancer. A higher prevalence and incidence of developing cancer and diseases associated with HPV have been observed in individuals infected with the human immunodeficiency virus (HIV). The natural history of HPV infection has not been completely elucidated, as well as the immune response that occurs as coinfection with HIV/HPV, particularly in the anal mucosa. Objective: To analyze the HPV prevalence and clinical, epidemiological, and behavioral data in a cohort of HIV-seropositive individuals from the National Institute of Infectious Diseases, FIOCRUZ, RJ. Methods: The study included a total of 114 individuals from the histopathological diagnosis of anal biopsy. PCR and sequencing was performed for HPV DNA identification in anal discharge. Statistical analysis was performed using SPSS 15.0 software. Results: Patients Infected with HIV with anal intraepithelial neoplasia (AIN) II/III had nadir CD4 + <50 cells/mm³ compared to normal patients (p=0.01). The most prevalent HPV types in the anal secretion (by Papillocheck) were HPV 16 (29.2%), followed by HPV 52 (23.1%), both high-risk oncogenic, followed by HPV 44 and 55 (21.5%) that are low-risk type. A total of 53.3% HIV-infected individuals analyzed have already been exposed to the four HPV types targeted by the current quadrivalent vaccine (MSDm – HPV types 6, 11, 16, and 18). Conclusion: The data suggest that vaccination against HPV could be regarded as a prophylactic measure to reduce the risk of anal intraepithelial lesions in HIV-infected individuals.